Recent advances in pyrazole synthesis employing diazo compounds and synthetic analogues - Chandrasekharan, Sanoop P; Dhami, Anamika; Kumar, Sandeep; Mohanan, Kishor (Organic & biomolecular chemistry, 2022)
Pyrazole is an essential structural component of many pharmaceuticals and agrochemicals. The synthesis of pyrazoles has been a subject of intense research for several decades. Many transformations are now available to conveniently access pyrazoles from readily available starting materials. Conventionally, the synthesis of pyrazoles involves the condensation reaction of hydrazines with 1,3-dicarbonyl compounds or their synthetic equivalents and 1,3-dipolar cycloaddition reactions of diazo compounds with dipolarophiles. The present review provides comprehensive information on the development of synthetic approaches to access pyrazoles via [3 + 2] cycloaddition reactions of diazo compounds and their synthetic equivalents. This review summarizes the recent developments in the construction of pyrazoles using diazo compounds, nitrile imines and their synthetic equivalents.